2017
DOI: 10.1111/mcn.12473
|View full text |Cite
|
Sign up to set email alerts
|

“Those who care much, understand much.” Maternal perceptions of children's appetite: Perspectives from urban and rural caregivers of diverse parenting experience in Bangladesh

Abstract: Appetite in children is an important determinant of nutritional intake and growth. The information used by caregivers to understand children's appetite can help inform infant and young child feeding promotion and appetite assessment. We conducted a qualitative study to (a) explore maternal perceptions and responses to children's appetite and (b) to identify how these factors differ by type of caregiver, level of maternal experience, and urban versus rural context. We used purposive sampling to recruit mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Most of the participants in our study were housewives (78%), were from rural areas (60%) and belonged to a nuclear family (64%). Previous studies have found that urban mothers have more access to accurate information on child feeding but less time to implement them, whereas rural women have more time to recognize the children's appetite cues but have minimal access to proper feeding information 19 .…”
Section: Resultsmentioning
confidence: 98%
“…Most of the participants in our study were housewives (78%), were from rural areas (60%) and belonged to a nuclear family (64%). Previous studies have found that urban mothers have more access to accurate information on child feeding but less time to implement them, whereas rural women have more time to recognize the children's appetite cues but have minimal access to proper feeding information 19 .…”
Section: Resultsmentioning
confidence: 98%
“…The primary objective of the study was to see the changes in appetite status of stunted children after receiving nutritional intervention. Prior studies have assessed the use of an appetite score based on food consumption, whereas the present study measured appetite using a previously validated interview-based tool [ 28 , 30 ]. The results of this study suggest that stunted children in Bangladesh receiving a nutrition intervention comprised of FS and PS had measurably increased appetite over a period of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Our qualitative findings indicate that caregiver's perceptions of complementary feeding practices could also vary among different areas and could thus contribute to inconsistent patterns of IYCF practices across programme areas. A study recently conducted in Bangladesh illustrates that complementary feeding practices are related to mothers' perceptions (Naila et al, 2018).…”
Section: Discussionmentioning
confidence: 99%